Influence of the deposition parameters on the nanolamella periodicity of chemical vapor deposited Ti1-xAlxN - Saringer, Christian; Tkadletz, Michael; Thurner, Josef; Czettl, Christoph; Schalk, Nina (Materials letters, 2021)
•Nanolamellae were found for a wide range of deposition parameters.•The lamella periodicity is not influenced by the rotation speed of the gas feed.•Increased pressure and decreased temperature result in a larger periodicity. Owing to its extraordinary nanolamellar microstructure, chemical vapor deposited Ti1-xAlxN has gained considerable interest in the recent years. However, the formation mechanism of the nanolamellae is not yet understood and is currently subject of intense research. In this publication we have deposited Ti1-xAlxN coatings at varying temperature, pressure and rotation speed of the central gas feed. Transmission electron microscopy has been conducted in order to quantify the lamella periodicity and correlate it with the deposition parameters. This work demonstrates that nanolamellae can be obtained over a wide range of deposition parameters and, more importantly, that the periodicity does not seem to depend on the gas feed rotation but can be correlated with deposition temperature and pressure.